HER2-targeted antibody-drug conjugate induces host immunity against cancer stem cells. Issue 5 (20th May 2021) - Xia, Leiming; Wen, Lu; Qin, You; Dobson, Hannah E.; Zhang, Tao; Comer, Frank I.; Hinrichs, Mary Jane; Oberst, Michael D.; Coats, Steven R.; Chang, Alfred E.; Liu, Yuanyuan; Bao, Yangyi; et al.
Summary: We previously tested HER2-targeted antibody-drug conjugates (ADCs) in immunocompromised (SCID) mice, precluding evaluation of host immunity, impact on cancer stem cells (CSCs), and potential benefit when combined with PD-L1 blockade. In this study, we tested HER2-targeted ADC in two immunocompetent mouse tumor models. HER2-targeted ADC specifically inhibited the growth of HER2-expressing tumors, prolonged animal survival, and reduced HER2 + and PD-L1 + cells. ADC + anti-PD-L1 antibody augmented therapeutic efficacy, modulated immune gene signatures, increased the number and function of CD3 + and CD19 + tumor-infiltrating lymphocytes (TILs), induced tumor antigen-specific immunological memory, stimulated B cell activation, differentiation, and IgG1 production both systemically and in the tumor microenvironment. In addition, ADC therapy modulated T cell subsets and their activation in TILs. Furthermore, HER2-targeted ADC reduced the number and tumorigenicity of ALDH hi CSCs. This study demonstrates that HER2-targeted ADC effectively targets ALDH hi CSCs and this effect is augmented by co-administration of anti-PD-L1 antibody. Graphical abstract: Highlights: HER2-targeted ADC shows anti-tumor activity in immune-competent mouse models HER2-targeted ADC induces humoral and cellular immunity and immunological memory The ADC inhibits tumor growth and prolongs survival by targeting ALDH high CSCs HER2-targeted ADC augments the therapeutic efficacy of anti-PD-L1 antibody Abstract : A major challenge for current cancer management is the relapse of the disease due to CSCs that are resistant to traditional therapies. Here, Xia and colleagues show that HER2-targeted ADC targets both bulk tumor cells and ALDH high CSCs via inducing anti-tumor cellular and humoral immune responses and immunological memory.